(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article provides general information about world and national tourism; innovative approaches in the development of tourism; world experience and features of its application in national tourism; there is information about the connection of information and communication technologies to the field of tourism and their role in the development of tourism. "Smart tourism" is also covered.